NCOG-25. THROMBOCYTOPENIA LIMITS THE FEASIBILITY OF SALVAGE LOMUSTINE CHEMOTHERAPY IN RECURRENT GLIOBLASTOMA: A SECONDARY ANALYSIS OF EORTC 26101. (14th November 2022) - Le Rhun, Emilie; Oppong, Felix Boakye; van den Bent, Martin; Wick, Wolfgang; Brandes, Alba; Taphoorn, Martin; Platten, Michael; Idbaih, Ahmed; Clement, Paul; Preusser, Matthias; Golfinopoulos, Vassilis; Gorlia, Thierry; et al.
Abstract: BACKGROUND: Thrombocytopenia represents the main cause of stopping chemotherapy for toxicity during the treatment of glioblastoma. Here we explored the incidence and prognostic implications of lomustine modification for thrombocytopenia in recurrent glioblastoma. METHODS: We retrospectively analysed thrombocytopenia, its consequences for treatment delivery, and associations with outcome in the phase II and III parts of EORTC 26101, a randomized trial to define the role of lomustine versus bevacizumab versus their combination in recurrent glioblastoma. RESULTS: 225 patients were treated with lomustine alone (median 1 cycle) (group 1) and 283 patients with lomustine plus bevacizumab (median 3 lomustine cycles) (group 2). 129 patients (57%) in group 1 and 187 (66%) in group 2 experienced at least one episode of thrombocytopenia; 36 patients (16%) in group 1 and 93 patients (33%) in group 2 had their treatment modified for thrombocytopenia. Lomustine was discontinued for thrombocytopenia in 16 patients (7.1%) in group 1 and in 38 patients (13.4%) in group 2. Patients with MGMT promoter-methylated glioblastoma treated with lomustine alone experienced more lomustine treatment modification than patients with tumors without MGMT promoter methylation. On adjusted analysis accounting for major prognostic factors, lomustine modification induced by thrombocytopenia was associated with inferior progression-free survival (PFS) in patients with MGMT promoter-methylated tumors in both groups, suggesting a link to insufficient lomustine exposure. This effect was noted for overall survival, too, but only for group 2 patients. Patients with MGMT promoter-unmethylated tumors who experienced dose modification for thrombocytopenia had longer PFS and overall survival, and this effect was driven largely by group 2 patients. CONCLUSION: Drug-induced thrombocytopenia is a major limitation to adequate exposure to lomustine in patients with recurrent glioblastoma. Its association with survival suggests that mitigating thrombocytopenia to allow enhanced lomustine exposure in patients with MGMT promoter methylated tumors might improve outcome.